The complete chloroplast genome sequence of Elaeocarpus braceanus: the first Celastraceae plastome. Issue 3 (2nd July 2020) - Wang, Qinghua; Su, Junwu; Li, Yunqin; Yuan, Xiaolong; Zhou, Hong; Wang, Yi
Abstract: The first complete chloroplast genome (cpDNA) sequence of Elaeocarpus braceanus was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 158, 225 bp in length, contains a large single-copy region (LSC) of 85, 731 bp and a small single-copy region (SSC) of 17, 654 bp, which were separated by a pair of inverted repeats (IR) regions of 27, 420 bp. The genome contains 133 genes, including 88 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. Further phylogenomic analysis showed that E. braceanus clustered in a clade in Celastrales order.